The Rule of Law: Measurement and Deep Roots - Jerg Gutmann; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2016)
This paper does three things. First, based on a limited number of theoretically established dimensions, it proposes a new de facto indicator for the rule of law. It is the first such indicator to take the quality of legal norms explicitly into account. Second, using this indicator we shed new light on the relationship between the rule of law and the political system of a country. Third, because political systems hardly predetermine the rule of law level of a country, we investigate the roots of the rule of law. As theory on this specific question is scarce and the rule of law is closely associated with income levels, we draw on a topical literature that deals with the fundamental causes of economic development. Our findings suggest that specific determinants of long-run development operate via the rule of law, whereas others are not related to the rule of law at all.
Keywords: B41; C81; C82; H11; K00; O17; O43; O57; 330; Rule of Law; Democracy; Dictatorship; Economic Development; Geography; Institutions